(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
In this article, the longevity of the elderly and the elderly is important in furthering the culture of life, in other words, in shaping their healthy lifestyle. One of the most important determinants of a healthy lifestyle is proper nutrition.